GSK-3β suppresses the proliferation of rat hepatic oval cells through modulating Wnt/β-catenin signaling pathway - JI Xiao-ke; XIE Yuan-kang; ZHONG Jun-qiao; XU Qi-gang; ZENG Qi-qiang; WANG Yang; ZHANG Qi-yu (Acta Pharmacologica Sinica; Vol 36, No 3 (March 2015): Acta Pharmacologica Sinica, 2017)
Aim: Glycogen synthase kinase 3β (GSK-3β) plays a crucial role in hepatic biology, including liver development, regeneration, proliferation and carcinogenesis. In this study we investigated the role of GSK-3β in regulation of growth of hepatic oval cells in vitro and in liver regeneration in partially hepatectomized rats. Methods: WB-F344 cells, the rat hepatic stem-like epithelial cells, were used as representative of oval cells. Cell viability was examined using a WST-8 assay. The cells were transfected with a recombinant lentivirus expressing siRNA against GSK-3β (GSK-3βRNAiLV) or a lentivirus that overexpressed GSK-3β (GC-GSK-3βLV). Adult rats underwent partial (70%) hepatectomy, and liver weight and femur length were measured at d 7 after the surgery. The expression of GSK-3β, phospho-Ser9-GSK-3β, β-catenin and cyclin D1 was examined with immunoblotting assays or immunohistochemistry. Results: Treatment of WB-F344 cells with the GSK-3β inhibitor SB216763 (5 and 10 μmol/L) dose-dependently increased the levels of phospho-Ser9-GSK-3β, but not the levels of total GSK-3β, and promoted the cell proliferation. Knockout of GSK-3β with GSK-3βRNAiLV increased the cell proliferation, whereas overexpression of GSK-3β with GC-GSK-3βLV decreased the proliferation. Both SB216763 and GSK-3βRNAiLV significantly increased the levels of β-catenin and cyclin D1 in the cells, whereas GSK-3β overexpression decreased their levels. In rats with a partial hepatectomy, administration of SB216763 (2 mg/kg, ip) significantly increased the number of oval cells, the levels of phospho-Ser9-GSK-3β, β-catenin and cyclin D1 in liver, as well as the ratio of liver weight to femur length at d 7 after the surgery. Conclusion: GSK-3β suppresses the proliferation of hepatic oval cells by modulating the Wnt/β-catenin signaling pathway.